Sei sulla pagina 1di 3

Random set theory

Theorem 1. Recursion theorem

For each set A, a A and F such that

: A A there exists unique function h

h : ω A

h(0) = a

h(n + ) = F (h(n))

Proof. We start by deﬁning a acceptable function.

v : ω A is acceptable iﬀ

1. 0 dom(v)

2. n ω, n + dom(v) =v(n + ) = F (v(n))

=

v(0) = a

We call a set of acceptable function K and deﬁne

h := K

We claim that h is a function we are looking for. We need to prove four things

1. h is a function. Let S be a set of natural numbers at which there is no more than one candidate for h(n).

S := {n ω : ! y A : n, y h}

We will show that dom(S ) = ω by showing that dom(S ) is induc- tive. If h 1 (0) = y 1 , y 2 it implies there exists two function v, v such that

v(0) = y 1 v (0) = y 2

but then y 1 = a = y 2 . That means 0 dom(S ). We proceed by induction:

Suppose h 1 (n + ) = {y 1 , y 2 }, again we have v, v and

y 1 = v(n + ) = F (v(n)) = F (v (n)) = v (n + ) = y 2

We conclude that h is a function.

1

 2. h is acceptable. Clearly h(0) = 0 since { 0, a } is acceptable function. Lets assume n + ∈ dom(h). Then there must be some acceptable v such that v(n + ) = F (v(n)) then { n, v(n) } ∈ h and h is acceptable. 3. dom(h) = ω. We will show that dom(h) = ω by showing that h is inductive. Clearly 0 ∈ dom(h) since { 0, a } is an acceptable function. Suppose k ∈ dom(h). If k + ∈ dom(h) we are done, otherwise consider v = h ∪ { k + , F (h(k)) } Since h is acceptable, v also is, but then v ⊆ h which implies v = h. 4. h is unique.

Uniqueness follows by simple induction. Suppose there are two function h, g ﬁtting the deﬁnition. Proceed by induction:

h(0) = g(0)

and inductive step:

h(n + ) = F (h(n)) = F (g(n)) = g(n + )

Theorem 2. Any Peano system N, S, e is isomorphic to ω, + , . That is, there exists bijection h : ω N such that

h(0) = e

h(n + ) = S(h(n))

Proof. Such function exists (and is unique) by recursion theorem. We only need to show that h is bijection. To show range(h) = S we use Peano induction postulate. We only need to show h(x) = h(y ) =x = y Let

T := {n ω : m ω : h(m) = h(n)

=

m = n}

We will show that T is inductive. We know h(0) = e, so we have to show that m : h(m + ) = e. We have

h(m + ) = S(h(m))

2

but x N : S(x)

Now we need to show

= e.

n T

=

n + T

So suppose n T . Let h(n + ) = h(m ) since m Then

S(h(n)) = h(n + ) = h(m + ) = S(h(m))

That leaves h(n) = h(m), which, by inductive hypothesis gives n =

m.

= 0 we can rewrite as h(n + ) = h(m + ).

3